Modelling and Observation of Exhaust Gas Concentrations for Diesel Engine Control - Blanco-Rodriguez, Dr.-Ing. David (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
XVII, 190 p. 89 illus., 1 illus. in color.